The philosophy of architectural ordering principles - Salura, Purnama (International Journal of Engineering and Technology, 2018)
Architectural ordering principles were always discussed by academics and architectural practitioners. Until now no one had sharply and specifically analyzed the architectural ordering principles. There was also no one had put forward the philoso-phy, theory that underlied the architectural ordering principle. Thus, architectural ordering principle became an important issue to be studied in depth. This theoretical research aimed to reveal the whole relation between architectural ordering principles with the concept, theory, philosophy that was supported it. The study analyzed three architectural theories that prioritized ordering principles. These three theories applied as case studies. This research succeeded in putting forward a new framework of relatively complete architectural ordering principles ranging from the philosophical, theoretical, to the underlying concepts. The result of the research was expected to be useful as a new reading tool of architectural ordering principles. Similarly, it was expected to be useful to be used as a relatively complete architectural design teaching tool. The results of this study is open to be elaborated and developed continuously.Â Â